Identification of phytochemicals and mineral nutrients of selected Malaysian plant extracts and its effects on seed priming of maize - Han, Mingzhao; Kasim, Susilawati; Uddin, Md Kamal; Abdullah, Halimatul Saadiah; Reza, Shah Ahmed; Mohd Shuib, Effyanti (Universiti Putra Malaysia Press, 2024)
Plants contain a variety of phytochemicals, which act as natural bioactive compounds to help plants enhance abiotic tolerance and promote growth. Therefore, plant extracts are considered to have great potential as environmentally friendly biostimulants in sustainable agriculture. This study aimed to identify the phytochemical compounds and quantify nutrients present in three plant extracts, namely Euphorbia hirta, Polygonum minus, and Eleusine indica, as well as to explore the effect on the growth of maize seedlings (Zea mays L.). The plant powder was extracted using methanol, followed by a solid-liquid extraction procedure. The phytocompounds were analyzed by liquid chromatography-mass spectrometry, while mineral nutrients were quantified using inductively coupled plasma. Five concentrations of plant extracts, i.e., 5, 15, 25, 50, and 100%, were designed to evaluate seed germination and priming. The result showed that 53, 45, and 39 phytocompounds were identified from E. hirta, P. minus, and E. indica, respectively, and classified into different chemical groups (such as flavonoids and amino acids) and rich nutrients (for example, N, P, and K). Besides, P. minus and E. hirta extracts with lower concentrations (5 and 15%) showed a positive effect on germination, shoot length and fresh weight, and the Highest concentration (100%) of E. hirta and E. indica extracts exhibited strong toxicity. This study emphasizes that weed extracts containing abundant secondary metabolites and nutrients can be used as natural biostimulants for maize seed priming.